2021
DOI: 10.14710/jkli.20.1.53-58
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemakaian Kelambu, Kawat Kasa dan Kondisi Geodemografis Terhadap Kejadian Malaria di Kabupaten Batu Bara

Abstract: Latar Belakang: Malaria merupakan salah satu penyakit menular yang menjadi masalah global. Malaria sering menimbulkan kejadian luar biasa dan berakibat pada penurunan kualitas hidup, ekonomi serta mengakibatkan kematian. Penelitian ini bertujuan untuk mengkaji hubungan penggunaan kelambu dan kawat kasa dengan kejadian malaria serta analisis spasial di Kabupaten Batu BaraMetode: Jenis penelitian ini adalah observasional analitik dengan disain matched case control terhadap umur dan jenis kelamin dan analisis spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
2
1
2
Order By: Relevance
“…The results showed that the habit of using mosquito nets with a p-value of 0.101 was not proven to cause malaria. This study is not in line with the research of Rahayu Lubis, which proves that people who do not sleep using mosquito nets are at risk of malaria 2.8 times compared to those who sleep with mosquito nets (Lubis et al, 2021).…”
Section: Risk Factor Analysis Of Habitual Use Of Mosquito Nets With T...contrasting
confidence: 87%
“…The results showed that the habit of using mosquito nets with a p-value of 0.101 was not proven to cause malaria. This study is not in line with the research of Rahayu Lubis, which proves that people who do not sleep using mosquito nets are at risk of malaria 2.8 times compared to those who sleep with mosquito nets (Lubis et al, 2021).…”
Section: Risk Factor Analysis Of Habitual Use Of Mosquito Nets With T...contrasting
confidence: 87%
“…Kelambu dan Kejadian Malaria di Indonesia [7,8,10,11,13,14,[19][20][21][22][23][24][25][26][27] Pada Forest Plot diketahui hasil random effect model mewakili perkiraan Odds Ratio (OR) sebesar 95% CI dengan hasil 0,58 dan rentang -0,212 -1,370. Hasil Forest plot ini menunjukkan bahwa nilai OR yang ditemukan adalah (e 0.58 ) adalah 1,786.…”
Section: Gambar 3 Forest Plot Perilaku Penggunaanunclassified
“…Artinya terdapat hubungan antara perilaku pemakaian kelambu dan Kejadian malaria. Orang yang tidur tidak menggunakan kelambu di daerah tyang terdapat penularan malaria berisiko 2,8 kali lebih besar tertular dibandingkan dengan orang yang tidur dengan menggunakan kelambu [24] . Penelitian serupa juga dilakukan Rangkuti dan didapatkan hasil p=0,000 dan OR 3,8.…”
Section: Tabel 4 Egger's Test Perilaku Penggunaan Kelambu Dan Kejadia...unclassified
“…26 Widiastuti and Lesmana in Kulon Progo Yogyakarta province reported the contrast that knowledge was not related to adherence to using LLINs this was because even though the community had gained knowledge through counseling, and media information, there were still many other factors beyond knowledge to comply with using LLINs such as attitudes and perceptions of people who have a sense of belonging discomfort and feeling of heat while inside LLINs. 27 Previous studies have explained that the highest risk factor influencing the incidence of malaria is the use of LLINs (p=0.001, OR=12.98), 28 (OR=2.8), 29 which means that the risk of malaria is more significant in people who do not install LLINs compared to people who install LLINs while sleeping. Other risk factors that were also reported were the type of wall of the house, individual activities to go out at night, use of wire netting, and trust with the behavior of using LLINs.…”
Section: Figure Properly Installed Mosquito Nets and In-depth Intervi...mentioning
confidence: 99%
“…Other risk factors that were also reported were the type of wall of the house, individual activities to go out at night, use of wire netting, and trust with the behavior of using LLINs. [28][29][30][31] Simanjorang and Kodim 32 in Manalu Sangihe islands, North Sulawesi province, found that most respondents (98%) had good knowledge of LLINs and adhered to using LLINs at night (83.1%), around 96.1% installed LLINs correctly, around 85.7% of respondents maintained and washed LLINs, and about 93.9% were exposed to direct sunlight. Currently, the LLINs owned by the community are mosquito nets with insecticide LLINs (96.8%) and ordinary mosquito nets (3.2%).…”
Section: Figure Properly Installed Mosquito Nets and In-depth Intervi...mentioning
confidence: 99%